Differentiating motives for nonmedical prescription stimulant use by personality characteristics. (January 2019) - Thiel, Alexandra M.; Kilwein, Tess M.; De Young, Kyle P.; Looby, Alison
Abstract: Nonmedical prescription stimulant use (NPS) is increasing, particularly among college students. College students typically engage in NPS for cognitive enhancement, recreational, and appetite/weight-related purposes; however, little research has used these motives to identify specific risk for, or consequences of, NPS. Moreover, there may be unique risk factors for motive-specific NPS that have yet to be explored, such as relevant personality traits (i.e., distress tolerance, impulsivity, and perfectionism) that are associated with NPS in general. Therefore, this study aimed to examine whether NPS users and nonusers could be differentiated via facets of impulsivity, perfectionism, and distress tolerance, and whether users could be further differentiated by reported motive for use based on these traits. Midwestern university undergraduate students ( N = 668) who were enrolled in a psychology research pool completed an online survey assessing demographics, NPS and motives, and measures of distress tolerance, impulsivity, and perfectionism. Participants were primarily female (78%) and aged 18–54 ( M = 20.10, SD = 3.19) years. Univariate and multivariate analysis of variance tests revealed associations between lifetime NPS and higher impulsivity, higher perfectionism, and lower distress tolerance. Further tests revealed NPS for appetite/weight-related purposes was associated with lower distress tolerance, while NPS for recreational purposes was associated with higher impulsivity. These findings contribute novel information regarding NPS motives and personality constructs. This information may aid in comprehensive identification of high-risk individuals for NPS and inform the development of specialized prevention and intervention efforts. Highlights: Observed NPS motives include cognitive, recreational, and appetite/weight-related. Lifetime NPS relates to impulsivity, perfectionism, and distress tolerance. NPS for appetite/weight-related purposes is uniquely related to distress tolerance. NPS for recreational purposes is uniquely associated with impulsivity. Cognitive enhancement motives were unrelated to all personality variables.